(Re)conceptualizing "Polydrug Use": Capturing the Complexity of Combining Substances. (December 2019) - Hakkarainen, Pekka; O'Gorman, Aileen; Lamy, François; Kataja, Kati
The use of multiple psychoactive substances is a widespread phenomenon among people who use drugs. Yet the concept of polydrug use is poorly defined in the social sciences. As a result, theoretical and empirical knowledge of polydrug use is underdeveloped; approaches to measuring polydrug use are inconsistent; and understandings of the cultural meanings of combining substances are limited. This article draws on a collaborative synthesis of three qualitative case studies of polydrug use from four countries: Australia and France, Finland, and Ireland. All three studies explored the practice of substance combination, or "combos" using the lens of intentionality, functionality, and social setting. In addition, the studies shared a common concern with teasing out the rationale for substance combining, and the controls used to balance pleasures with risks, beyond the simple physiological or sensory effects of substances. Our analysis leads us to recommend that a standard definition of polydrug use be adopted for future social science research—that is, the ingestion of two or more substances in combination, at the same time or in temporal proximity, so that the effects of different substances overlap. For analytical purposes, we suggest two subcategories: simultaneous and sequential intake. Moreover, we contend that it is the intention, meaning, and socio-structural context underpinning the use of substance combinations that is central to understanding polydrug use. Consequently, we suggest an adaptation of Zinberg's seminal concept to one of "drug combo, set, and setting" to incorporate an analysis of the effects of using substances together, or in sequence within a short time frame.